1998
DOI: 10.1006/qres.1998.1974
|View full text |Cite
|
Sign up to set email alerts
|

All Toba Tephra Occurrences across Peninsular India Belong to the 75,000 yr B.P. Eruption

Abstract: A controversy currently exists regarding the number of Toba eruptive events represented in the tephra occurrences across peninsular India. Some claim the presence of a single bed, the 75,000-yr-old Toba tephra; others argue that dating and archaeological evidence suggest the presence of earlier Toba tephra. Resolution of this issue was sought through detailed geochemical analyses of a comprehensive suite of samples, allowing comparison of the Indian samples to those from the Toba caldera in northern Sumatra, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 21 publications
8
104
0
1
Order By: Relevance
“…Their REE content and chondritenormalized pattern of 1883 Krakatau pumice normally show depletion in light REE as compared to YTT pumice, but heavy REE contents of both Krakatau and YTT pumice are similar. The REE patterns of pumice of the YTT eruption and glass shards of YTT origin are closely comparable to that reported from the CIOB, Northern Sumatra, the South China Sea, the western continental margin of India and the Indian subcontinent (Shane et al, 1995;Pattan et al, 2001;Westgate et al, 1998;Song et al, 2000), further supporting YTT as source for Group-II pumice ( Krakatau eruption (0.15), as reported by Mandeville et al (1996) and Pearce (1982), whereas the mean La/Rb ratio of Group II pumice from the CIOB matches with that of YTT caldera (0.33) as reported by Chesner (1998). The plot of Nb/Y versus La/Rb shows two distinct fields such as the 1883 Krakatau and YTT eruptions, further confirming their different sources (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Their REE content and chondritenormalized pattern of 1883 Krakatau pumice normally show depletion in light REE as compared to YTT pumice, but heavy REE contents of both Krakatau and YTT pumice are similar. The REE patterns of pumice of the YTT eruption and glass shards of YTT origin are closely comparable to that reported from the CIOB, Northern Sumatra, the South China Sea, the western continental margin of India and the Indian subcontinent (Shane et al, 1995;Pattan et al, 2001;Westgate et al, 1998;Song et al, 2000), further supporting YTT as source for Group-II pumice ( Krakatau eruption (0.15), as reported by Mandeville et al (1996) and Pearce (1982), whereas the mean La/Rb ratio of Group II pumice from the CIOB matches with that of YTT caldera (0.33) as reported by Chesner (1998). The plot of Nb/Y versus La/Rb shows two distinct fields such as the 1883 Krakatau and YTT eruptions, further confirming their different sources (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Mishra and Rajaguru (1994) suggested the young age assignment was at odds with Lower Palaeolithic artefacts associated with the Bori tephra and as such, multiple Toba tephra deposits of various ages must be preserved across India. Westgate et al (1998) reported glass shard geochemistry from sites in India supporting the conclusion that the tephra distributed across India is YTT. However, it should be noted that glass shard chemistry from the different Toba tephra is similar and whereas tephra correlation to Toba is possible, correlation to specific eruptions is more problematic.…”
Section: The Toba Caldera and Distal Tephra In Indiamentioning
confidence: 70%
“…Distally, tephra from the Toba eruptions has been documented in Malaysia (Scrivenor, 1930), the Bay of Bengal (Ninkovich et al, 1978), the East China Sea (Lee et al, 2004), the Indian Ocean (Pattan et al, 2001), and sites across the peninsula of India (Westgate et al, 1998). The general NW distribution of Toba tephra (Fig.…”
Section: The Toba Caldera and Distal Tephra In Indiamentioning
confidence: 88%
“…Before searching for signs of the Toba in the Antarctic ice, it would be important to know if there were only one or several eruptive events from this volcano during this time period. Westgate et al (1998) unequivocally demonstrated that all the presently known Toba tephra occurrences in Peninsular India belong to the 73 kyr BP Toba super-eruption. There were however several known eruptions of this volcano during the Quaternary (see Westaway et al, 2011, for an exhaustive review).…”
Section: Glaciological Implicationsmentioning
confidence: 88%
“…The Toba super-eruption ∼73 kyr ago is one of the most important of the last million years (e.g. Petraglia et al, 2007), with regional consequences such as climate cooling and deforestation in South Asia (Williams et al, 2009;Williams, 2011), though the global environmental impact of this eruption is debated (Robock et al, 2009). Indeed, some of the environmental changes occurring after the Toba event may have been caused by the strong concurrent millennial-scale climate variability, the Toba super-eruption reportedly being coincident with the end of Greenland Interstadial (GI) 20 (Zielinski et al, 1996).…”
Section: 72mentioning
confidence: 99%